Tunnels : with 25 great projects for kids - Moore, Jeanette (Explore your world! (White River Junction, Vt.)., 2018)
"Moles, beavers, rabbits . . . these animals burrow tunnels in the ground every day! What other kind of creature makes tunnels? Humans! In Tunnels! With 25 Science Projects for Kids, kids ages 7 to 10 explore the fascinating world of passageways beneath the ground, dug deep within the earth through soil and rock. But why dig through rock to make a tunnel? Tunnels give people a way to travel and transport goods from one place to another. Readers learn about the engineering and construction that goes into every tunnel made, whether it's being dug under roads, under oceans, or under cities. Kids form a foundational learning about the laws of physics that govern our world and discover how engineers use these laws to design tunnels that withstand the test of time, weight, and earthquakes. Controlling groundwater, drilling through rocks, and removing earth are just a few tasks workers must face. STEM projects for kids, including creating a tunnel maze, designing a series of tunnels on graph paper, and experimenting with Newton's laws of motion, offer a unique, interactive learning experience, while links to primary sources offer ample opportunity for further student-led exploration. Fun facts, engaging illustrations, timeline, glossary, and resources keep kids wanting to learn more about the engineering design process. Tunnels! is part of a set of four Explore Engineering books. In the Explore Engineering series, readers ages 7 to 10 learn the physics behind the things they build: Why does a tower of blocks eventually fall? Why does a tunnel sometimes cave in? Through a series of focused, science-minded activities that require critical thinking paired with creative trial-and-error attempts at building, readers develop foundational understanding of the physics that guides the building and maintenance of bridges, canals, dams, tunnels, and skyscrapers. Other titles in the Explore Engineering set include Bridges!, Canals and Dams!, and Skyscrapers! " --